Risk Management in Border Inspection - Hillberry, Russell; Karabay, Bilgehan; Tan, Shawn W. (World Bank, Washington, DC, 2020)
As part of their commitments under the World Trade Organization’s Agreement on Trade Facilitation, many developing countries are set to adopt risk management, a strategy for selecting import shipments for inspection. This paper formalizes key enforcement issues related to risk management. It argues that the complexities of international trade oversight mean that inspecting agencies lack certainty about the conditional probability that a given shipment will not comply with import regulations. Ambiguity of this sort is likely to be important in developing countries that lack the sophisticated information technology (IT) used in advanced risk management systems. This paper show empirically that infrequent shipments have conditionally higher inspection rates, a finding that is consistent with the ambiguity hypothesis. This paper formalizes a role for ambiguity in a theoretical model of border inspection. Finally, the paper calibrates the model and shock the ambiguity parameters to illustrate the consequences of an IT -driven improvement in risk management capabilities for search and compliance.